Optimizing Display Design to Enhance Visual Experience at Sintuk War Museum - Fauziyah Afni; Della Oktavinoarti; Intan Tursina (Gorga : Jurnal Seni Rupa, 2026)
The Sintuk War Museum in Padang Pariaman Regency plays a crucial role in preserving and disseminating the narrative of local historical struggles. However, the utilization of the museum’s interior, particularly its display system, has not been optimized, resulting in limited visual readability, inadequate collection grouping, and a diminished visitor experience. This study seeks to optimize the museum display design to enhance the quality of visual presentation and visitors’ comprehension of historical content. This research employs a design thinking approach comprising five stages: empathize, define, ideate, prototype, and test. Data were collected through direct observation, interviews with museum management, visual analysis of the exhibition space, and a literature review pertaining to museum display design. The collected data were analyzed using SWOT analysis to identify strengths, weaknesses, opportunities, and threats as the foundation for design development. The study generated several alternative display design concepts, which were subsequently evaluated through prototyping and user feedback. The selected display design prioritizes visual clarity, efficient space utilization, collection safety, and the reinforcement of historical narratives through focused lighting and systematic object grouping. The proposed design is anticipated to enhance visitors’ focus, comfort, and comprehension of the exhibited collections. This study provides design recommendations that integrate aesthetic, functional, and educational aspects, rendering them pertinent for the development of display systems in historical museums with comparable characteristics.